Developments in tidal energy proceedings of the third conference on tidal power organized by the Institution of Civil Engineers and held in London on 28-29 November 1989. (Thomas Telford, 1990)
This is an analysis of the issues involved in assessing the viability of barrage construction with particular reference to the Severn barrage and the Mersey tidal project. The book explores the projects from site investigation and promotion to turbine generators and energy production.